2010
DOI: 10.1515/hf.2010.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sample preparation on NIR spectroscopic estimation of chemical properties of Eucalyptus urophylla S.T. Blake wood

Abstract: Many studies have successfully applied near infrared (NIR) spectroscopy to estimate important wood traits. Some of them have reported the effects of wood surfaces on NIR spectra information and their influence on the performance of the predictive model. However, limited information is available concerning the effect of sample preparation on the model performance to estimate chemical properties in Eucalyptus wood. Hence, the aim of this study was to investigate the influence of the milling procedure, particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…They concluded that size reduction improved the stability of spectra, and consequently, the predictive diagnostics of models developed. Hein et al 16 also had a similar conclusion, but they added that the difference between lumber and milled wood was more significant than the difference between particle sizes of milled wood.…”
Section: Introductionmentioning
confidence: 87%
“…They concluded that size reduction improved the stability of spectra, and consequently, the predictive diagnostics of models developed. Hein et al 16 also had a similar conclusion, but they added that the difference between lumber and milled wood was more significant than the difference between particle sizes of milled wood.…”
Section: Introductionmentioning
confidence: 87%
“…The influence of particle size on the NIR spectra is not consensual: some authors stated that the particle size influences the prediction error (the R 2 in lignin prediction of coniferous biomass diminished from 0.96-0.99 to 0.90 in 80 and 20-40 mesh, respectively) [20], whereas others reported that particle size effects are not important, and coarse powder produces calibration as good as fine powder, without any specific variation of R 2 [21]. Furthermore, it is known that spectra pre-processing, such as the use of derivatives, can minimize the effect of sample preparation [22].…”
Section: Methodsmentioning
confidence: 99%
“…trees coming from the same experimental plantation were previously evaluated for wood density 27 and chemical composition. 28…”
Section: Methodsmentioning
confidence: 99%